IMPLEMENTASI PRINSIP-PRINSIP GOOD GOVERNANCE PADA PEMERINTAHAN DESA BUKIT MAS KECAMATAN PANTAR KABUPATEN ALOR - Abang, Frengkison; Djaha, Ajis S. Adang; Pandie, Ardy Y. (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
Good governance is part of the reform agenda which is basically an ideal condition that is expected to be realized in every aspect of government, including at the village government level. This study aims to analyze the implementation of the principles of good governance in Bukit Mas Village, Pantar District, Alor Regency. The method used in this research is a qualitative approach with data collection techniques, namely interviews, observation and documentation. The data sources used are primary and secondary data, and data analysis consists of data collection, data reduction, data presentation, conclusion d rawing and data verification. The informants in this study consisted of the community and the Bukit Mas village government. This research focuses on identifying the four main principles of good governance including accountability, transparency, participation, and the rule of law. The results showed that the application of the principles of good governance is still not optimal, which has an impact on the low level of public trust in the village government.